Documentation of Cultural Properties in Tabaco City, Philippines through Cultural Mapping - Edgardo Besmonte; Al Besmonte; Alwin Calig; Michael Cobilla (Camarines Sur Polytechnic Colleges, 2022)
This research project was conducted to document the cultural properties of Tabaco City, Philippines, through Cultural Mapping. It sought to generate baseline data for cultural statistics on tangible and intangible heritage, natural heritage, significant personalities, and cultural institutions. This study adopted the Cultural Mapping Methodology of the National Commission for Culture and the Arts. Participants of this cultural mapping were composed of 11 mappers who were trained to do the heritage documentation. Ethnography, community immersion, in-depth interviews, document analysis, participant observation, historiography, and photo documentation, were used in data collection. Findings revealed that the cultural mapping project in Tabaco City, Philippines was able to document and provide an inventory of the cultural properties of the place that showcase the city's rich culture that could be used as baseline data in the formulation of promotional activities, conservation projects, policies, and legislation to fully safeguard and protect the city's heritage resources. This study recommends that the output of this cultural mapping must be disseminated to schools and libraries so that the community, especially the students, researchers, and cultural workers, can raise their awareness of the city's rich culture and thorough research on the documented cultural properties must be conducted. Moreover, the government and other stakeholders must strengthen their efforts to foster awareness, appreciation, and protection of the cultural properties of Tabaco City, Philippines.